The persistence of poverty and joblessness in US households - Angela Rachidi (American Enterprise Institute (AEI), 2018)
While annual poverty rates and monthly unemployment figures are useful, from a policy perspective, it matters whether individuals experience poverty and unemployment for short periods of time or persistently.
Keywords: J; 330; long-term unemployment; Poverty